Detection of a ryanodine receptor target‐site mutation in diamide insecticide resistant fall armyworm, Spodoptera frugiperda. Issue 1 (8th July 2019) - Boaventura, Debora; Bolzan, Anderson; Padovez, Fernando EO; Okuma, Daniela M; Omoto, Celso; Nauen, Ralf
Abstract: BACKGROUND: Fall armyworm (FAW), Spodoptera frugiperda (J.E. Smith), a major lepidopteran pest in Latin and North America, has very recently invaded the continents of Africa and Asia. FAW has evolved resistance to different insecticides and transgenic corn expressing Bacillus thuringiensis (Bt) toxins. Here, we investigated the extent and mechanisms of resistance to diamide insecticides in a Brazilian field‐collected FAW strain selected using chlorantraniliprole. RESULTS: Continuous laboratory selection of a field‐collected FAW strain with chlorantraniliprole resulted in resistance ratios of 225‐fold and > 5400‐fold against chlorantraniliprole and flubendiamide, respectively, when compared with a susceptible strain. Pre‐exposure to different synergists known to inhibit detoxification enzymes did not result in significantly increased larval toxicity, suggesting a minor role for metabolic resistance. Sequencing of the FAW ryanodine receptor (RyR) C‐terminal domains II to VI revealed a single nucleotide polymorphism, resulting in a I4734M mutation recently said to confer target‐site resistance to diamides in lepidopteran pests. Genotyping by pyrosequencing of field‐collected FAW larvae sampled in the 2018 crop season suggests a low resistance allele frequency. Furthermore, we developed a fluorescent polymerase chain reaction (PCR)‐based allelic discrimination assay for rapid genotyping of field‐collected FAW samples, because diamides are increasingly used in Bt−/non‐Bt corn. CONCLUSIONS: Recently, the identified RyR mutation has been shown to confer field resistance in other lepidopteran pests such as diamondback moth, tomato leafminer and striped rice stem borer. The developed PCR‐based allelic discrimination assay will help to monitor the frequency and future spread of diamide resistance allele in FAW field populations and help to implement appropriate resistance management measures. © 2019 Society of Chemical Industry Abstract : We identified a I4790M ryanodine receptor mutation in diamide insecticide resistant fall armyworm selected with chlorantraniliprole. This mutation confers diamide resistance in other lepidopteran pests and should be carefully monitored.